2017
DOI: 10.3346/jkms.2017.32.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Entire Mitochondrial DNA Sequencing on Massively Parallel Sequencing for the Korean Population

Abstract: Mitochondrial DNA (mtDNA) genome analysis has been a potent tool in forensic practice as well as in the understanding of human phylogeny in the maternal lineage. The traditional mtDNA analysis is focused on the control region, but the introduction of massive parallel sequencing (MPS) has made the typing of the entire mtDNA genome (mtGenome) more accessible for routine analysis. The complete mtDNA information can provide large amounts of novel genetic data for diverse populations as well as improved discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
6
17
0
Order By: Relevance
“…(), Ramos et al (), nor Park, Cho, Seo, Lee, Kim, and Lee () reported any heteroplasmic hotspots; the observation being identical to the results of our study. Furthermore, the overall pattern of point heteroplasmic substitution at the level of above 10% (with a little prevalence of heteroplasmic substitution in the coding region than in the control region) in the normal colon cells reported here is similar to those observed for blood (Li et al., ; Parson et al., ; Ramos et al., ; Park et al., ) or saliva samples (Li et al., ). Nevertheless, when one takes into account the low level variants (below 10% level) from our study, the overall spectrum of heteroplasmic substitutions showed that heteroplasmy in normal colon cells hits predominantly the D‐loop region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(), Ramos et al (), nor Park, Cho, Seo, Lee, Kim, and Lee () reported any heteroplasmic hotspots; the observation being identical to the results of our study. Furthermore, the overall pattern of point heteroplasmic substitution at the level of above 10% (with a little prevalence of heteroplasmic substitution in the coding region than in the control region) in the normal colon cells reported here is similar to those observed for blood (Li et al., ; Parson et al., ; Ramos et al., ; Park et al., ) or saliva samples (Li et al., ). Nevertheless, when one takes into account the low level variants (below 10% level) from our study, the overall spectrum of heteroplasmic substitutions showed that heteroplasmy in normal colon cells hits predominantly the D‐loop region.…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, the mtDNA mutational spectrum reconstructed by us for 100 normal specimens (analyzed population sample increased by 50 samples compared with our previous report, Skonieczna et al., ) is similar to that observed in healthy individuals from different populations. Indeed, different studies validated to detect the minority variant at the level of about 10%, showed that point heteroplasmy occurs in about 24%–28% of individuals (Li et al., ; Parson et al., ; Ramos et al., ; Park et al., ). Similarly, in our dataset, the 10% threshold of the minority variant detection enabled us to show heteroplasmic substitutions in 21% of normal tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…Both sites follow a 4‐mer poly‐A‐stretch (AAAA) region. Studies have suggested that it is the homopolymer stretch that lowers the efficiency of reads in this region . Low coverage in homopolymer regions of the Ion PGM™ or other MPS platforms has been described, as have high coverages in amplicons with few homopolymeric repeats .…”
Section: Resultsmentioning
confidence: 99%
“…However, the control region covers only 7% of the human mitochondrial genome and limits the resolution of matrilineal and ancestry inferences . Whole genome sequencing offers additional sequences from which mitochondrial haplogroups can be determined to the highest resolution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation